The Principal’s Supervision to Improve Teacher Professionalism - Yazid, Hendri; Marsidin, Sufyarma; Rifma, Rifma (Universitas Negeri Malang, 2021)
This study aimed at determining the program, implementation, evaluation, and looking at the supporting and inhibiting factors faced by the school principal of Madrasah Aliyah in carrying out their duties as supervisors. The method used in this study is qualitative with a descriptive approach. This study is conducted in Madrasah Aliyah Negeri 3 Padang. Meanwhile, for data collection techniques, this study employs observation, interviews, and documentation with the research subject of madrasah principal, vice-principal of the madrasah, and teachers totaling 49 people. Data analysis is executed by reducing, displaying, drawing conclusions, and verifying data. It was found that the supervision program was established at the beginning of the year through meeting activities involving all madrasah personnel which was carried out according to a predetermined schedule. Supervision is carried out on individual teachers and groups with class visits, teacher meetings, group discussions, exchange of experiences, and seminars. Supervision evaluation is carried out at the end of each semester by improving the goals that have not been achieved and making improvements in the preparation of the next program. The supporting factor for the implementation of supervision is the teacher responding positively and the establishment of a good relationship between the madrasah principal and the teachers so that it raises the awareness of the teachers to improve their abilities. Meanwhile, the obstacles in this study were the implementation of this supervision are due to the busyness of the madrasah principal and the absence of the teacher when the supervision is carried out.